Research and comparison of solid-liquid phase equilibrium and ternary phase diagrams of 1-(3-nitrophenyl)ethanone + 1-(4-nitrophenyl)ethanone in different solvents. (September 2019) - Li, Rongrong; Jin, Yanxian; Wang, Xiaoqiang; Zhan, Shiyun; Zhu, Yuwei; Zheng, Mengmeng; Zhao, Jia; Han, Deman
Highlights: The solid-liquid phase equilibrium for ternary 1-(3-nitrophenyl)ethanone + 1-(4-nitrophenyl)ethenone + methanol/n-propanol. Constructing isothermal ternary phase diagrams at different temperature. NRTL model was used to correlate the mutual solubility. The results of correlation were evaluated by statistical approach. Abstract: The ternary phase equilibrium for 1-(3-nitrophenyl)ethanone and 1-(4-nitrophenyl)ethanone in methanol or n -propanol were determined at 298.15, 308.15 K and 318.15 K under atmospheric pressure in this work. Based on the measured mutual solubility data, the isothermal ternary phase diagrams were constructed. In each ternary phase diagram, there were one co-saturated point, two boundary curves, and three crystalline regions. The crystallization region of 1-(3-nitrophenyl)ethanone was about the same as 1-(4-nitrophenyl)ethanone at all researched temperatures. The NRTL model was used to correlate the solubility of the ternary 1-(3-nitrophenyl)ethanone + 1-(4-nitrophenyl)ethanone + solvents. The correlation results were evaluated by the values of relative average deviation ( RAD ) and root-mean-square deviation ( RMSD ), and their values were 4.18 × 10 −2 and 3.60 × 10 −3, respectively. The calculated results via this model were all acceptable for ternary solid-liquid phase equilibrium. The ternary phase diagram obtained will play an important part in separating the mixture of 1-(3-nitrophenyl)ethanone and 1-(4-nitrophenyl)ethanone.